Teamwork for Innovation in Sub-Saharan Africa - Seriki, Hannah Titilayo (Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2007)
Innovation is an essential success factor needed to ensure and extend the competitiveness of organisations. The quality of teamwork plays an important role as it determines the success of innovation teams. Whereas most insights concerning the dynamics of work groups come from North American or Western European environments, Hannah Titilayo Seriki concentrates on teams operating within the complex societal context of sub-Saharan Africa. The author develops a multi-level theory of African teams' innovative performance and regards the team as a sub-system of the organisation, which is subjected to societal influences. She compares the insights gained from case studies in Nigeria and in South Africa with findings from two Germanic European cases. The results of her study imply that managers can actively and consciously influence the way their organisations pass on societal forces to their sub-units. Distinct differences between European and African cases are found, especially in the areas of team leadership and motivation.